Renal pseudotumor mimicking renal cell carcinoma in an elderly patient with ovarian carcinoma: Case report and literature review - Maximilian Althammer, MD; Thomas Kroencke, MD; Josua A. Decker, MD (Radiology Case Reports)
This case report is about an 84-year-old female patient with a history of high-grade serous ovarian carcinoma who was diagnosed with a renal pseudotumor. Initial imaging in February 2023 showed signs of a renal cell carcinoma and possible lung metastases. A CT-guided biopsy and histopathological analysis ruled out malignancy and confirmed a benign inflammatory pseudotumor. This case underlines the importance of a biopsy to avoid unnecessary treatments such as nephrectomy and emphasizes the worth of comprehensive diagnostic evaluation. These steps are important to prevent unnecessary surgical interventions, overtreatment and to focus on effective, targeted therapy for the actual underlying pathology.